A study of some Oxford schoolmen of the middle of the fourteenth century with special reference to Worcester Cathedral MS. F. 65. - Forte, SL (1947)
Worcester Cathedral Library MS.F.65 contains a collection of academic exercises held in the schools of Theology at Oxford, in the second half of the fourteenth century. Although perhaps this manuscript does not contain the richness of some other similar collections of Questiones, such as Assisi MSS.158 and 196, there cannot be any doubt that it throws light on the academic life of the University of Oxford. It shows how the statutes were worked out in practice, how the disputations were held, and throws not a little light on the customs and Masters of the University of Oxford during the period covered by the collection. Naturally enough, one would have wished to find in this manuscript fuller information on these matters; however, I have had the good fortune of supplementing its data with the information met with in St. John's College, Cambridge, MS.103, and Bodley 692, even if these two are of a later date. The whole work is divided into two separate volumes: … Continued in thesis ...